G53 Current Practise Relating to Fluid Bolus Administration in Critically Ill Children. (4th June 2013) - Sambandamoorthy, G; Inwald, D; Peters, M; Ramnarayan, P
Abstract : Aim: To establish the frequency, amount and the diagnostic reasons for fluid bolus administration in children referred to a paediatric intensive care (PIC) retrieval service Methods: Retrospective case notes review of all referrals to a PIC retrieval service between May and October 2012 (6 months). Data collected included demographic details, reason for PIC referral, and total amount of bolus fluids given at referral. Blood products were excluded from the total fluid bolus calculations. In children retrieved by the service, additional data on total amount of fluid boluses given during retrieval and patient acuity (need for invasive ventilation, vasoactive agent use and PIM-2 score) were analysed. Categorical data are reported as counts (percentages) and continuous data as mean (standard deviation) or median (inter-quartile range) as appropriate. Results: During the 6-month study period, 1031 referrals were made to the retrieval service. At referral, 180 patients had received ≥20mls/kg of fluid boluses (17.5%) and 54 had received ≥40mls/kg (5.2%). The main diagnoses for which children were given fluid boluses ≥20mls/kg were sepsis (30%) and status epilepticus (21%). 548 children (53%) were retrieved to PICU. Patients receiving ≥40mls/kg by PICU admission had a median age of 14 months (IQR 2–47), were mostly male (60%), requiring invasive ventilation (98.3%) and vasoactive agents (61.5%). The median PIM-2 predicted risk of mortality was 10% (IQR 6–19%). A summary of total fluid administered at various time points is provided below in cases where a PIC retrieval team was mobilised (n = 548): Conclusion: Our audit provides valuable baseline data on the frequency, amount and timing of fluid bolus administration in critically ill children with a range of diagnoses. At a time when fluid therapy is a subject of considerable debate, this study provides useful information on current practise and may help in the design of future interventional trials in this area.